Exploring and Identifying Postmodern Features in Demon Slayer’s Infinity Castle - Clairine Valerie; Fasya Ayudhea; Qazka Tabita Ritonga (Journal of Innovative and Creativity, 2025)
The purpose of this study was to explore the postmodern elements in Demon Slayer: Kimetsu no Yaiba, focusing on the Infinity Castle Arc as a representation of fragmented narrative and visual excess in contemporary anime. Using a qualitative descriptive method within the framework of postmodern theory, the research analyzes the arc’s narrative structure, spatial design, and symbolic motifs to identify the features of postmodernism, including fragmentation, hyperreality, metafiction, and pastiche. The analysis reveals that the Infinity Castle functions not merely as a setting but as a reflection of postmodern instability, its constantly shifting architecture disrupts linear storytelling and challenges conventional narrative logic. Moreover, the arc’s use of visual exaggeration and emotionally charged imagery creates a sense of hyperreality, where spectacle and feeling become inseparable from meaning. The presence of metafiction and intertextuality further demonstrates how the series blurs the boundaries between reality and fiction, tradition and innovation, and local and global cultural influences. Through these aspects, Demon Slayer constructs a layered narrative world that mirrors the complexity and uncertainty of postmodern experience. Ultimately, this study argues that the Infinity Castle Arc transforms the series into a postmodern text that reflects the fluid nature of identity, truth, and perception in today’s media landscape.